Improving Computing Education Research through Valuing Design: Exploring alternatives to existing research systems and methods. - Shapiro, R. Benjamin; DesPortes, Kayla; DiSalvo, Betsy (Communications of the ACM, 2023)
The article explores how to improve computing education research (CER) with design. CER aims to develop knowledge about how to create new universes that better support problem-solving, creativity, and communication by people. Other topics discussed include how computational technologies can be the "cultural building materials" for designers, researchers, and educators, the opinion that programming languages are the least usable but the most powerful interfaces ever invented, and how the improvement of teaching tools can improve accessibility and outcome.